The Africans: A triple heritage : Global Africa, inteview with Ali Mazrui - Mazrui, Ali AlAmin (The Annnenberg/CPB Collection, 1986)
Illustrates African contributions to contemporary culture, including the significance of the African diaspora, particularly in North America, and examines the continuing influence of the superpowers on the affairs of the continent. Also known as: Africa in the world. Closed captioned for the hearing impaired. Target audience: General.